Changes in Melanocortin Expression and Inflammatory Pathways in Fetal Offspring of Nonhuman Primates Fed a High-Fat Diet - Grayson, B. E. (The Endocrine Society, 2010)
The hypothalamic melanocortin system, which controls appetite and energy expenditure, develops during the third trimester in primates. Thus, maternal nutrition and health may have a profound influence on the development of this system. To study the effects of chronic maternal high-fat diet (HFD) on the development of the melanocortin system in the fetal nonhuman primate, we placed adult female macaques on either a control (CTR) diet or a HFD for up to 4 yr. A subgroup of adult female HFD animals was also switched to CTR diet during the fifth year of the study (diet reversal). Third-trimester fetuses from mothers on HFD showed increases in proopiomelanocortin mRNA expression, whereas agouti-related protein mRNA and peptide levels were decreased in comparison with CTR fetuses. Proinflammatory cytokines, including IL-1β and IL-1 type 1 receptor, and markers of activated microglia were elevated in the hypothalamus, suggesting an activation of the local inflammatory response. Fetuses of diet-reversal mothers had normal melanocortin levels. These results raise the concern that chronic consumption of a HFD during pregnancy, independent of maternal obesity and diabetes, can lead to widespread activation of proinflammatory cytokines that may alter the development of the melanocortin system. The abnormalities in the fetal POMC system, if maintained into the postnatal period, could impact several systems, including body weight homeostasis, stress responses, and cardiovascular function. Indeed, the HFD offspring develop early-onset excess weight gain. These abnormalities may be prevented by healthful nutrient consumption during pregnancy even in obese and severely insulin-resistant individuals.